PENGARUH RASIO SOLVABILITAS DAN RASIO PROFITABILITAS TERHADAP PENGUKURAN KINERJA KEUANGAN PERUSAHAAN DI PT BCA Tbk - Joni Tesmanto; Naftalia Meilani Angeline (Lembaga Pengembangan Kinerja Dosen, 2022)
The use of financial ratios will explain and provide an overview of the bank's financial position and see the bank's wealth. Of the Solvency ratio (CAR) and Profitability ratio (ROA, ROE, NIM) on financial performance (profit). The data used is secondary data with data collection techniques through indirect observation. CAR regression coefficient on earnings is negative with the results of the t-test -5.312 < t table 2.04. The regression coefficient of ROA on earnings is positive with the results of the t-test 2.409 > t table 2.043 which means that ROA has an effect on earnings. profit. The NIM regression coefficient on earnings is positive with the t-test result of 0.770 < 2.043, which means that NIM has no effect on earnings. Overall F count of 8,560 > F table 2.70 which means that CAR, ROA, ROE and NIM together have an influence on profit.